Relationships between teachers' practices and learners' mathematical identities. Issue 3 (16th March 2021) - Gardee, Aarifah
ABSTRACT: The field of mathematics education has seen an increase in research focused on the concept of identity, with many researchers focusing on the role of teacher pedagogies in shaping learners' identities and their participation in and engagement with mathematics. In this paper, the actual and narrated practices of two teachers, which incorporate teachers' pedagogical approaches and social relationships with learners, are analysed in relation to how they provided opportunities for the construction of learner identities. The paper draws on data that were collected over two years in the form of videotaped lessons, field notes and audiotaped semi-structured interviews with teachers and learners. Data were analysed using qualitative data analysis techniques. The analysis suggests a relationship between the teachers' actual and narrated practices, with the teachers' practices influencing the kinds of identities constructed by learners in their classrooms, in terms of learners' enjoyment of learning mathematics and their willingness to participate in and become fully fledged members of their classroom community.